A Qualitative Study of Epiphytic Algae (Diatom) on Some Aquatic Plants in Al-Auda Marshes Within Maysan Province / Southern Iraq - Baghdad Science Journal (مجلة بغداد للعلوم)
The study conducted on the compositions of epiphytic diatoms on three taxa of aquatic plants were selected (Phragmites australis Trin ex stand , Ceratophyllum demersum L. and Typha domengensis Pers) in three sites within Al-Auda Marsh, from autumn 2013 to summer 2014 . The study was measured physical and chemical factors of all the study sites, such as: air temperature, power of hydrogen (pH), electrical conductivity (EC), salinity (S‰), total hardness(TH), dissolved oxygen (DO), and plant nutrient. The results showed that water of marsh was oxygenated and it was very hard. A total of 111 taxa of phytoplankton were identified, which belonged to 13 families and 26 genus (one family and two genus of centric diatoms, 12 families and 26 genus of pennate diatoms). One of the diatoms taxa was recorded in the present study is new to Iraqi flora,the new record of diatom include one taxa of Achnanthidiaceae family (Achnanthes exigua var. constricta ). The results showed that epiphytic diatoms community have a moderate diversity according to the Shannon-Weaver Index, which ranged between (0.24-2.57).